Et fysisk objekt fra kardinal Nicolaus Breakespears legat til Norden 1152-54 - Jahr, Ernst Håkon (Scripta Neophilologica Posnaniensia, 2019)
A physical object from Cardinal Nicolaus Breakspear’s legation to Scandinavia, 1152-54 This article gives an account of the background and discovery of the only remaining physical object from Cardinal Nicolaus Breakspear’s legation to Scandinavia 1152–54 on behalf of Pope Eugenius III. The Pope had invested in Cardinal Breakspear the authority to negotiate and make decisions on the organisation of the church in the three Scandinavian kingdoms: Denmark, Norway and Sweden. Until then, the church in the whole of Scandinavia was under the archbishop of Lund. Lund at that time was part of Denmark, not of Sweden, as it is today. During his time in Norway, Cardinal Breakspear (c. 1100–1159) reorganised the Norwegian church under its own archbishop in Nidaros (Trondheim), and established a new Norwegian diocese in Hamar. The Pope’s plan was in addition to establish another archbishopry in Sweden, but that could not yet be achieved due to internal Swedish disagreements. The Sweden church, therefore, remained under the archbishop of Lund. When Cardinal Breakspear left Scandinavia from the town of Lomma close to Lund, he somehow must have dropped a lead seal which was attached to a letter from the Pope. This seal was then accidentally refound in the middle of the 1980s when Mr. Per Olsson dug in his garden in Lomma. He thought he had found an old coin and kept it in a drawer in his house. Per Olsson’s son, Magnus Linnarsson, later found out that the seal was from Pope Eugenius III. It is highly probable that this seal today is the only remaining physical artifact of Cardinal Breakspear’s legation to Scandinavia 1152–54. Cardinal Breakspear soon after his return to Rome became the new Pope under the name (H)Adrian IV. Until Pope John Paul II visited Norway in 1989, Nikolaus Breakspear is the only Pope ever to have set foot in Norway, and that happened before he was elected Pope. The seal is since 2011 included in the collections of Lund’s Historical Museum.